Karakteristik Kuat Tarik Beton dengan Penambahan Serat Sabut Kelapa dan Silica Fume sebagai Substitusi Semen - Debby Sinta Devi; Utari Sriwijaya Minaka; Fathoni Usman; Happy Bunga Nasyirahul Sajidah; Raihan Rasyid (Institut Teknologi Garut, 2026)
This study evaluates the effect of integrating coconut coir fiber at contents of 2 percent, 2.5 percent, and 3 percent, along with 5 percent silica fume, on the splitting tensile strength performance of concrete. The experimental results show that the 2 percent coconut coir fiber proportion provided the optimal performance, with a tensile strength value reaching 3.12 MPa, or an increase of 12.5 percent compared to the control concrete, which had a tensile strength of 2.5 MPa. Although fiber additions at higher contents of 2.5 percent and 3 percent still contributed to mechanical strength, a significant decline in concrete mixture workability was observed. The synergy between silica fume through its pore-filling effect and natural fibers proved effective in optimizing concrete density and ductility. This study concludes that the combination of these two materials can produce innovative concrete that is stronger and more environmentally friendly as a future construction material solution.